1998
DOI: 10.1007/s000110050341
|View full text |Cite
|
Sign up to set email alerts
|

Increased release of ATP from endothelial cells during acute inflammation

Abstract: These results show that non-damaged endothelial cells release ATP under experimental inflammatory conditions and support an early role of extracellular ATP in the inflammatory process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
115
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(120 citation statements)
references
References 23 publications
(32 reference statements)
3
115
0
2
Order By: Relevance
“…It has been shown that P2 activation leads to increases in concentration of intracellular calcium and PGE2 release (Naemsch et al, 2001). ATP, which activates this pathway, is typically released by bone, endothelial and epithelial cells and fibroblasts under stress conditions, acting as a DAMP/alarmin (Bodin & Burnstock, 1998;Burnstock, 1999;Furuya, Sokabe & Furuya, 2005;Grygorczyk & Hanrahan, 1997;John & Barakat, 2001;Katsuragi & Migita, 2004;Katz, Boland & Santillan, 2006;Kerkweg & de Groot, 2005;Milner et al, 1992;Milner et al, 1990b;Ohata et al, 1997;Patel et al, 2005;Romanello et al, 2001;Sauer, Hescheler & Wartenberg, 2000;Yamamoto et al, 2003).…”
Section: P2x7 Receptor: a Possible Mediator Of Orthodontic Mechanotramentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that P2 activation leads to increases in concentration of intracellular calcium and PGE2 release (Naemsch et al, 2001). ATP, which activates this pathway, is typically released by bone, endothelial and epithelial cells and fibroblasts under stress conditions, acting as a DAMP/alarmin (Bodin & Burnstock, 1998;Burnstock, 1999;Furuya, Sokabe & Furuya, 2005;Grygorczyk & Hanrahan, 1997;John & Barakat, 2001;Katsuragi & Migita, 2004;Katz, Boland & Santillan, 2006;Kerkweg & de Groot, 2005;Milner et al, 1992;Milner et al, 1990b;Ohata et al, 1997;Patel et al, 2005;Romanello et al, 2001;Sauer, Hescheler & Wartenberg, 2000;Yamamoto et al, 2003).…”
Section: P2x7 Receptor: a Possible Mediator Of Orthodontic Mechanotramentioning
confidence: 99%
“…It can be activated (opened) after binding to extracellular ATP, which is a danger signal from cells under mechanical stress (Bodin & Burnstock, 1998;Milner et al, 1990a;Schneider et al, 2006). Opening of the channel causes the accumulation of intracellular calcium and the release of inflammatory mediators such as PGE2, IL-1α and IL-1β, all fundamental in the control of bone physiology (Brough et al, 2003;Ferrari et al, 2006;Gudipaty et al, 2003;Li et al, 2005;Lister et al, 2007).…”
Section: Orthodontic Mechanotransduction and The Role Of The P2x7 Recmentioning
confidence: 99%
“…Due to its size and high density of charge, ATP cannot permeate membranes. However, release of ATP has been observed from a variety of cells, including tumor cells and lymphocytes, as well as from virtually all tissues under conditions of hypoxia, ischemia, inflammation, and cell necrosis (5)(6)(7)(8). The sources of released ATP include exocytotic granula from secretory cells, release from lysed cells, and nonlytic release from cytoplasmatic stores.…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…ATP can be released from endothelium in response to increases in shear stress (Bodin et al, 1991) and from perivascular nerve terminals (Ralevic & Burnstock, 1998;Burnstock & Kennedy, 1986). In¯ammatory mediators, ischaemia, and damage to blood vessels also cause ATP release from endothelial cells, neutrophils, cardiomyocytes, erythrocytes and platelets (Borst & Schrader, 1991;Born & Kratzer, 1984;Bodin & Burnstock, 1998;Pearson & Gordon, 1985;Yang et al, 1994;Bergfeld & Forrester, 1992;Gordon, 1986;Ralevic & Burnstock, 1991;1998;Sprague et al, 1996;Olsson & Pearson, 1990). ATP is rapidly broken down to adenosine by endothelial ectonucleotidases (Pearson & Gordon, 1985).…”
Section: Introductionmentioning
confidence: 99%